2016
DOI: 10.1038/nchembio.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency and amplitude control of cortical oscillations by phosphoinositide waves

Abstract: Rhythmicity is prevalent in the cortical dynamics of diverse single and multicellular systems. Current models of cortical oscillations focus primarily on cytoskeleton-based feedbacks, but information on signals upstream of the actin cytoskeleton is limited. In addition, inhibitory mechanisms--especially local inhibitory mechanisms, which ensure proper spatial and kinetic controls of activation--are not well understood. Here, we identified two phosphoinositide phosphatases, synaptojanin 2 and SHIP1, that functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 49 publications
3
55
0
Order By: Relevance
“…In some cases, the similar phase relationships among various components has been documented. In mast cells, for example, F-actin zones correspond to troughs in PIP2 waves (Xiong et al, 2016). It remains to be determined whether these dynamic events are displayed by a few cell types under specific conditions or whether they are an unrecognized general feature of migrating cells and perhaps play further roles in cell physiology.…”
Section: The Signal Transduction “Excitable” Network or Stenmentioning
confidence: 99%
“…In some cases, the similar phase relationships among various components has been documented. In mast cells, for example, F-actin zones correspond to troughs in PIP2 waves (Xiong et al, 2016). It remains to be determined whether these dynamic events are displayed by a few cell types under specific conditions or whether they are an unrecognized general feature of migrating cells and perhaps play further roles in cell physiology.…”
Section: The Signal Transduction “Excitable” Network or Stenmentioning
confidence: 99%
“…There is strong evidence that phospholipid signalling is an integral part of this actin oscillator with a positive feedback loop in which F-actin activates PI3K. PI3K-dependent production of PIP3 phosphoinositides, integral constituents of the cell membrane, can in turn stimulate further F-actin production through Rac, which activates NPFs of Arp2/3 [47,48]. Khamviwath et al [24] have proposed a continuum model for actin waves based on a large number of molecular details of actin network dynamics and the PI3K pathway ( figure 7).…”
Section: Actin Waves Reveal Intrinsic Excitable Properties Of the Actmentioning
confidence: 99%
“…We previously showed that SHIP1, a PIP3 5-phosphatase is a molecular marker for the refractory phase of FBP17 waves (Xiong et al, 2016). To determine whether the difference in time of the clathrin onset was determined by the length of the refractory phase in the previous cycle, we imaged SHIP1 together with clathrin.…”
Section: Resultsmentioning
confidence: 99%
“…For cortical actin waves, molecular players that act upstream of actin, including Rho family GTPases and their activating lipid second messengers have been heavily investigated. These include Rac and phosphatidylinositol-3,4,5-trisphosphate (PIP3) in HL-60 neutrophils (Weiner et al, 2007), Rho in Xenopus eggs and starfish oocytes (Bement et al, 2015), PIP3 and phosphoinositide-3-kinase (PI3K) in Dictyostelium discoideum (Arai et al, 2010), and Cdc42 and PI3K in RBL-2H3 mast cells (Xiong et al, 2016). Because waves of Rho GTPase activation usually precedes actin waves and inactivation of these Rho GTPases could abolish actin waves, activation of Rho GTPases has been suggested to be involved in wave nucleation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation